2020
DOI: 10.7717/peerj.10551
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences show that only some bats can cope with noise-induced masking and distraction

Abstract: Anthropogenic noise is a widespread pollutant that has received considerable recent attention. While alarming effects on wildlife have been documented, we have limited understanding of the perceptual mechanisms of noise disturbance, which are required to understand potential mitigation measures. Likewise, individual differences in response to noise (especially via perceptual mechanisms) are likely widespread, but lacking in empirical data. Here we use the echolocating bat Phyllostomus discolor, a trained discr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…In the simulations, LMMs and LMs did not appear to give drastically different parameter estimates for fixed effects. Often researchers (sometimes nudged by peer-reviewers) cite this guideline of needing 5 levels before random effects inclusion as a reason why they were unable to use a mixed-effects model ( Bain, Johnson & Jones, 2019 ; Bussmann & Burkhardt-Holm, 2020 ; Evans & Gawlik, 2020 ; Gomes & Goerlitz, 2020 ; Zhao, Johnson-Bice & Roth, 2021 ). Although there is confusion over this recommendation, as some opt to use mixed-effects models despite this suggestion ( Latta et al, 2018 ; Fugère, Lostchuck & Chapman, 2020 ; Gomes, Appel & Barber, 2020 ; Allen et al, 2021 ), likely because of the numerous advantages that mixed-effects models offer ( Bolker, 2008 ; Kéry & Royle, 2015 ; Harrison et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the simulations, LMMs and LMs did not appear to give drastically different parameter estimates for fixed effects. Often researchers (sometimes nudged by peer-reviewers) cite this guideline of needing 5 levels before random effects inclusion as a reason why they were unable to use a mixed-effects model ( Bain, Johnson & Jones, 2019 ; Bussmann & Burkhardt-Holm, 2020 ; Evans & Gawlik, 2020 ; Gomes & Goerlitz, 2020 ; Zhao, Johnson-Bice & Roth, 2021 ). Although there is confusion over this recommendation, as some opt to use mixed-effects models despite this suggestion ( Latta et al, 2018 ; Fugère, Lostchuck & Chapman, 2020 ; Gomes, Appel & Barber, 2020 ; Allen et al, 2021 ), likely because of the numerous advantages that mixed-effects models offer ( Bolker, 2008 ; Kéry & Royle, 2015 ; Harrison et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in each of the above segments of quoted text, the authors suggest that at least five levels are needed for estimation of group-level, or among-population, variance . However, it is my observation that there is some confusion about this rule and it is often adhered to out of context, where authors or reviewers of ecological journals suggest that one cannot use random effects terms if they do not contain at least five levels ( Bain, Johnson & Jones, 2019 ; Bussmann & Burkhardt-Holm, 2020 ; Evans & Gawlik, 2020 ; Gomes & Goerlitz, 2020 ; Zhao, Johnson-Bice & Roth, 2021 ), although others are aware that this rule exists yet ignore it ( Latta et al, 2018 ; Fugère, Lostchuck & Chapman, 2020 ; Gomes, Appel & Barber, 2020 ; Allen et al, 2021 ). For context, within a small sample of the most recent articles in the journal Ecology ( N = 50), 18 articles mentioned 29 different random effects—only one of which (~3%) included fewer than five levels ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…abramus , indicating that pulse variation is not an adaptive response to counteract noise interference. Second, some bats show individual differences in echolocation pulse adjustments and feeding performance in the presence of anthropogenic noise, including free‐tailed bats ( Tadarida brasiliensis ) (Tressler & Smotherman, 2009 ), Daubenton’s bats (Luo, Siemers, et al, 2015 ), and pale spear‐nosed bats (Gomes & Goerlitz, 2020 ). In this case, it is expected that a small number of P .…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the level of spectrally non-overlapping airport noise was also a significant predictor of pulse duration and peak frequency in P. abramus, indicating that pulse variation is not an adaptive response to counteract noise interference. Second, some bats show individual differences in echolocation pulse adjustments and feeding performance in the presence of anthropogenic noise, including free-tailed bats (Tadarida brasiliensis) (Tressler & Smotherman, 2009), Daubenton's bats (Luo, Siemers, et al, 2015), and pale spear-nosed bats (Gomes & Goerlitz, 2020). In this case, it is expected that a small number of P. abramus within the population can tolerate high levels of airport noise and perform foraging activities at noisy sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have found that terrestrial species generally increase the minimum but not the maximum or peak frequencies of their vocalisations, as it is the lower frequency elements of vocalisations that are most likely to be affected by anthropogenic noise (Duquette et al, 2021;Kunc & Schmidt, 2021). Finally, individuals may alter the duration of their vocalisations during anthropogenic noise (Francis et al, 2011;Gomes & Goerlitz, 2020;Kunc & Schmidt, 2021;Potvin & Mulder, 2013), generally by increasing the length of their vocalisation to improve signal detection in the presence of increased noise (Brumm et al, 2004;Francis et al, 2011). Despite changes to the rate, amplitude, frequency, and duration of vocalisations being attributed to anthropogenic noise, few studies consider all of these parameters simultaneously (Nemeth & Brumm, 2009;Pearson & Clarke, 2018;Proppe et al, 2011;Sementili-Cardoso & Donatelli, 2021;Slabbekoorn & den Boer-Visser, 2006;Templeton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%